A Hybrid Power Mean Involving the Dedekind Sums and Cubic Gauss Sums - Jiayuan Hu; Yu Zhan; Qin Si (Journal of Mathematics)
The main purpose of this paper is using analytic methods and the properties of the Dedekind sums to study one kind hybrid power mean calculating problem involving the Dedekind sums and cubic Gauss sum and give some interesting calculating formulae for it.